Corpo e sexualidade nas redes sociais: O advento do ciberespaço (re)significando e (re)construindo a noção de “si” do sujeito contemporâneo - Santos, Fausi dos (2014)
This dissertation is part of the project “Education Observatory” of Unifran. It assumes that the discourse about the body and sexuality within the school, in most cases, is controlled or deleted or omitted for various reasons and circumstances. However, young people of high school, out of school, especially in social networks write about their bodies and their sexuality. Therefore, research that can observe and analyze what the discursive practices and identity are in relationship and internet sites, you can make allowances for thinking discourses about the body and sexuality within the school. Discursively analyze the Body and Sexuality as a gesture interpretation of thought in different fields of social utterance is not an easy task as bumps on the finding that the subjective production of meaning bordering varying effects in different eras, social and existential contexts. Any serious interpretive approach takes into account the different positions that the discursive subject and enunciator occupies in certain contexts and situations, hence the need to observe the body and sexuality as a given and not closed in on itself, conceptually fact, but as realities process at different times manifest effects of varying direction. In this sense, the central objective of this dissertation is to identify and discursively reflect the modes of reading and seeing the body and sexuality in social networks and analyze the effects of meaning that (re)signify and discursively (re)construct the notion of self in cyberspace. The corpus analysis configures itself, first, in the speeches of interaction between man and machine while informational and computational platform and then the discourse practices and productions of meaning that this interaction produces and develops in the form of man and enunciate your body subjectivise and their sexuality. A community that offers virtual relationship services as a way to understand the processes of self-presentation discursively produced by users of the network was analyzed. The community is entitled: Badoo. The theoretical framework utilizes the concepts established in the work of Michel Foucault, History of Sexuality, which will be a landmark because it reveals an essential tool in understanding the mechanisms of power and knowledge used by the company in the construction of utterances. These exert fundamental influences on the structuring of subjectivity or identity of the "sexual" subject. The Foucaultian concept of "subjugated subject" reinforces the hypothesis that the existence of social networks as a platform used in manifesting your desires and frustrations on topics related to sexuality (sexual orientation, gender discrimination, homophobia, body and sex), collaborates in the preparation enunciations denouncing significant changes in perception of self and the development of new devices manifestation of sexuality. Current informational and communicational machines are not content to convey representative contents, but also contribute to the making of new assemblages of enunciation (individual and/or collective). Other theoreticians are also used, such as: Eni P. Orlandi, Eva Illouz, Zygmunt Bauman, Denise Bernuzzi Sant'Anna, Giovanne Reale, Mary Del Priore, Peter N. Stearns, Dominique Maingueneau, Félix Guattari, Adauto Novaes. As the machinery of social networks used today as technology itself, which questions whether they exert influence in the context of preparation of utterances about sexuality and the body. And yet, as these machineries exert power to support the production of subjectivity? Thus, it is believed to establish some points of reflection to better understand the ways of reading and view sexuality and the body and hence the elaborate speeches on social networks and other platforms for producing and reading text. Keywords: body, sexuality, social networking, discursive practices; subjectivity